DIFFUSION INDUCED LI ISOTOPIC FRACTIONATION DURING THE COOLING OF MAGMATIC ROCKS: THE CASE OF PYROXENE PHENOCRYSTS FROM NAKHLITE METEORITES - Beck P.; Chaussidon M.; Barrat J.A.; Gillet Ph.; Bohn M. (My University, 2006)
Ion-microprobe was used to measure Li abundances and isotopic compositions in pyroxenes from three Martian meteorites belonging to the nakhlite family. The profiles performed across augite crystals from Northwest Africa 817 show a large isotopic zoning from crystal cores (?7Li ? 0?) to rims (?7Li ? +20?) while Li abundances are almost constant (?9.2 ?g/g). Unlike NWA 817, the pyroxene studied in the Miller Range 03346 nakhlite shows a zoning in Li abundance, with concentrations increasing from ?2.5 ?g/g in the core to ?9 ?g/g in the rim. The augite rim (?7Li = +7?) is slightly enriched in 7Li with regard to the core (?7Li = +4?), but most of the isotopic variations observed occur at an intermediate position along the profile, where ?7Li falls down to ?-11?. In the case of Nakhla, Li concentrations in augite increase from cores (?3.5 ?g/g) to rims (?6.5 ?g/g), while the ?7Li variation is restricted (i.e., between ?7Li = +6.0 and +12.6?). For the three meteorites the Li abundances were also measured in the groundmass, which was found to be enriched in lithium (?10 ?g/g). Conventional magmatic and post-magmatic processes such as alteration and fractional crystallization, fail to explain the dataset obtained on nakhlites. Degassing processes, which were previously proposed to explain the Li distribution in shergottite crystals, cannot result in the strong decoupling between Li abundances and isotopic composition observed in nakhlites. We suggest that the original magmatic Li distributions (concentrations and isotopic compositions) in nakhlites have been modified by diffusion of Li from the Li-rich groundmass towards the pyroxene crystals during sub-solidus cooling. Diffusion appears to have been efficient for NWA 817 and MIL 03346 but, apparently, did not produce a significant migration of Li in Nakhla, possibly because of the lower abundance of groundmass in the latter. Diffusion induced Li redistributions may also affect terrestrial porphyric rocks but very specific cooling rates are required to quench the diffusion profiles as observed in two of the present nakhlites. ? 2006 Elsevier Inc. All rights reserved.
Keywords: AUGITE; IGNEOUS ROCK; ISOTOPIC COMPOSITION; ISOTOPIC FRACTIONATION; LITHIUM; METEORITE; PHENOCRYST; PYROXENE